Chalcogenide Glass Hollow-Core Microstructured Optical Fibers - Shiryaev, Vladimir S. (Frontiers in Materials, 2015)
The recent developments on chalcogenide glass hollow core microstructured optical fibers (HC-MOFs) are presented. The comparative analysis of simulated optical properties for chalcogenide HC-MOFs of negative-curvature with different size and number of capillaries is given. The technique for the manufacture of microstructured chalcogenide preforms, which includes the assembly of the substrate glass tube and 8-10 capillaries, is described. Further trends to improve the optical transmission in chalcogenide NCHCFs are considered.